(untitled) - Jones, Daniel (Cambridge, 1998)
This edition of The Pronunciation of English incorporates the final results of Daniel Jones' lifelong study of English pronunciation usage. The book is the standard work on English phonetics and the name of its author will, in the words of Professor A. C. Gimson, 'remain in linguistic history as the great authority on the pronunciation of British English in the twentieth century'. The Pronunciation of English was written originally as a detailed description of the phonetics of English, presented from the point of vew of the native English-speaking student. However, it soon established itself as a standard textbook in universities where English is a foreign language, because it provides in a lucid and authoritative manner the basic information needed by foreign students of the language. Most of the book is devoted to a descriptive account of English pronunciation. This is followed by illustrative texts in phonetic transcription of Received Pronunciation and several regional varieties, Scottish and American pronunciation and reconstructions of Shakespearian and Chaucerian speech.
Keywords: English language,English language; Pronunciation,Problems, exercises, etc,Textbooks for foreign speakers